Marriage and the economy : theory and evidence from advanced industrial societies - Grossbard-Shechtman, Shoshana, 1948- (Cambridge University Press, 2003)
Marriage and the Economy explores how marriage influences the monetized economy as well as the household economy. Marriage institutions are to the household economy what business institutions are to the monetized economy, and marital status is clearly related to the household economy. Marriage also influences the economy as conventionally measured via its impact on labor supply, workers' productivity, savings, consumption, and government programs such as welfare programs and social security. The macro-economic analyses presented here are based on the micro-economic foundations of cost/benefit analysis, game theory, and market analysis. Micro-economic analysis of marriage, divorce, and behavior within marriages are investigated by a number of specialists in various areas of economics. Western values and laws have been very successful at transforming the way the world does business, but its success at maintaining individual commitments to family values is less impressive.